2006
DOI: 10.1021/bm060708r
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation of Polyester Blends Containing Atactic Poly(3-hydroxybutyrate). Biodegradation in Soil and Ecotoxicological Impact

Abstract: The degradation of poly[(R,S)-3-hydroxybutyrate], a-PHB, binary blends with natural PHB (n-PHB) and poly(L-lactic acid), PLLA, respectively, has been investigated in soil. In such a natural environment, a-PHB blend component was found to biodegrade. The degradation of a-PHB-containing blends proceeded faster than that of respective plain n-PHB and PLLA. The molecular weight decrease of the n-PHB component was higher, while the same rate of bioerosion of both components was observed for the a-PHB/n-PHB binary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…As a rule, blending has been known as a strategy of tailoring the properties of PHAs while maintaining biodegradability 67 . Blending of PHB and PHBV with other biopolymers including starch [89][90][91] , thermoplastic starch, PLA 92 , PCL 13,93,94 , and polyvinyl alcohol (PVOH) 91 are reported. In addition, there are some reports on PLA blending with different polymers e.g.…”
Section: Blendingmentioning
confidence: 99%
“…As a rule, blending has been known as a strategy of tailoring the properties of PHAs while maintaining biodegradability 67 . Blending of PHB and PHBV with other biopolymers including starch [89][90][91] , thermoplastic starch, PLA 92 , PCL 13,93,94 , and polyvinyl alcohol (PVOH) 91 are reported. In addition, there are some reports on PLA blending with different polymers e.g.…”
Section: Blendingmentioning
confidence: 99%
“…The authors conclude that the addition of a-PHB accelerates the process of degradation of natural PHB, and in the presence of mineral fertilizer, the erosion of all samples occurs faster than that without fertilizer. 30 Weng et al 31 studied the biodegradation of the P(3HB,4HB)/PLA blends with different compositions at different depths in real soil environments. The degraded residues of various samples demonstrated that P(3HB,4HB) was biodegraded into small molecular weight acids caused by erosion of microorganisms.…”
Section: Biodegradation Test-respirometric Testmentioning
confidence: 99%
“…Blending with other biopolymers has been considered as a way of tailoring the properties of PHAs while maintaining biodegradability (Ohashi et al, 2009). Mixtures of PHB and PHBV with other biopolymers have been reported by numerous authors and the polymers mentioned in recent studies include starch (Godbole et al, 2003;Reis et al, 2008;Zhang and Thomas, 2010), thermoplastic starch , poly-(L-lactic acid) (PLLA) (Furukawa et al, 2006;Rychter et al, 2006), polycaprolactone (PCL) (Lovera et al, 2007;Sanchez-Garcia et al, 2008), and polyvinyl alcohol (PVOH) (Olkhov et al, 2003).…”
Section: Overviewmentioning
confidence: 99%